Between embeddedness and otherness – internationalisation of grocery retailers in emerging markets - Lech Suwala; Elmar Kulke (Managing Culture and Interspace in Cross-border Investments, 2017)
Grocery retailing was, and is still often considered to be a prevailing domestic economic activity. Trends, however, are changing. In the meantime, an internationalization of grocery retailing, which took off at least 40 years ago allowed for the development of a coexistence of both domestic and international structures. Despite the unimpeded success of globalization's benefits in general retailing, the “big picture” in grocery retailing is - with a few exceptions - somehow different. Against this background, the chapter illustrates (a) dominant formats, (b) market entry modes, and (c) spatial expansion patterns of leading global grocery retailers in the first part. Moreover, it emphasises that the internationalisation of grocery retailers is not exclusively motived by classical Uppsala-Model arguments (socio-cultural and organizational proximity - the embeddedness issue), but also driven by flag-planting in remote countries (socio-cultural and organizational distance - the otherness issue). The otherness issue - or to put it in technical terms “liability of foreignness” or “liability of outsidership” had ambivalent effects. It led to both inclusion and exclusion processes (f.e. learning vs. elimination) for both regional actors and investors. Therefore, the chapter shows selected cases of effects of these ambivalent processes on different stakeholders within the grocery retail value chain (e.g suppliers, other retailers, consumers) in the second part. In a nutshell, every grocery retailer that had tried to expand to overseas markets failed as often as it has succeeded.
Keywords: L81; F23; O19; R30; 330; Internationalisation of Grocery Retailers; Retail Industry; Embeddedness; Otherness; Liability of Foreignness; Liability of Outsidership